Comparative study of biochemicals and antioxidant activities of two wild edible mushrooms Russula gnathangensis and Ramaria thindii from Sikkim Himalayas, India - Paul, Chandana; Das, Nirmalendu (Mushroom Research, 2021)
Wild edible mushrooms are utilized by ethnic people in rural communities of India as food and medicinal purposes. The aim of the present study was to estimate biochemical constituents and antioxidant activities of two wild edible mushrooms viz. Russula gnathangensis and Ramaria thindii isolated from Sikkim Himalaya. Methanolic extract of oven dried mushroom powders were used for the estimation of polyphenol, flavonoid, tannin, lycopene and β-carotene contents and determination of antioxidant activities though protein and carbohydrate contents were estimated using aqueous extracts. All the chemical constituents were measured on dry wt. basis. Protein contents of R. thindii and R. gnathangensis were 185.8 μg/mg and 164.7 μg/mg, respectively. R. thindii showed 191.7 μg/mg carbohydrate content whereas R. gnathangensis showed 140.5 μg/mg. Polyphenol and flavonoid contents of  R. thindii  were 7.9 μg/mg and 1.0 μg/mg, respectively whereas R. gnathangensis showed 4.25 μg/mg polyphenol and 0.75 μg/mg flavonoid contents. Tannin contents of R. thindii and R. gnathangensis were 2.35 and 1.46 μg/mg, respectively. R. thindii showed better lycopene content but both the species showed  similar amount of  β-carotene. Both the species showed high amount of antioxidant activities. These wild mushrooms may fulfill the nutritional requirement of the local ethnic people if properly conserved.